Human lymphoid tissue sampling for vaccinology - Kwiatkowska, Karolina M.; Mkindi, Catherine G.; Nielsen, Carolyn M. (Frontiers in Immunology, 2022)
Long-lived plasma cells (LLPCs) – largely resident in the bone marrow – secrete antibody over months and years, thus maintaining serum antibody concentrations relevant for vaccine-mediated immunity. Little is known regarding factors that can modulate the induction of human LLPC responses in draining lymph node germinal centres, or those that maintain LLPCs in bone marrow niches following vaccination. Here, we review human and non-human primate vaccination studies which incorporate draining lymph node and/or bone marrow aspirate sampling. We emphasise the key contributions these samples can make to improve our understanding of LLPC immunology and guide rational vaccine development. Specifically, we highlight findings related to the impact of vaccine dosing regimens, adjuvant/ vaccine platform selection, duration of germinal centre reactions in draining lymph nodes and relevance for timing of tissue sampling, and heterogeneity in bone marrow plasma cell populations. Much of this work has come from recent studies with SARS-CoV-2 vaccine candidates or, with respect to the non-human primate work, HIV vaccine development.